Increasing the heap leach efficiency of Uşak Kışladağ gold ore using nut shell as permeability aid - Bilen, Mehmet; Yilmaz, Serdar; Kizgut, Sait; Sirkeci, Ayhan Ali (Elsevier BV, 2020)
Abstract The objective of this study is to increase the gold recovery from the gold ore heaps of Usak Kisladag Gold Company adding nut shell as percolation enhancer. In the first step of this study, bottle roll experiments were carried out on the ore sample crushed below 18 mm, 10 mm, 2.36 mm and 74 μm. Gold recovery values obtained for bottle roll tests were 53%, 55%, 65% and 85% respectively for the particle sizes −18 mm, −10 mm, −2.36 mm and −74 μm respectively. The initial experiments provided information about the ultimate gold recovery that can be reached for the particle sizes studied. Following the bottle roll tests, column leach experiments were carried out for-18 mm (the original heap particle size) and −2.36 mm size fractions for a duration of 30 days. Gold recoveries of 48% and 40% were obtained for the size groups of −18 mm and −2.36 mm respectively. At the final stage of the study, the effect of nut shell addition on the gold recoveries was studied using column leach experimental set up. Test results showed that nut shell addition markedly increased the permeability of the ore and hence the leach efficiency. The increase in the finer particle size was more noticeable because of the increase in the permeability and decrease in the particle size. Gold recoveries for −2.36 mm particle size were 42%, 55% and 61% respectively when 2.5%, 5% and 10% nut shell by volume was added. Furthermore, no gold adsorption was observed on the organic substance.
Keywords: engineering and technology; other engineering and technologies